Mental health inequality between urban and rural youth under COVID-19 from survey data from China - Xiao, Yang (Frontiers in Public Health, 2024)
Background While health inequality has been the focus of past scholarly discussions, COVID-19’s outbreak and spread have provided a new arena for discussing health inequality, particularly in the context of urban–rural disparities in China. This paper explores the impact of COVID-19 on urban–rural health inequality, and the roles played by socioeconomic status and social capital. Methods A cross-sectional observational collected data on demographics, mental health, socioeconomic status, and social capital. An online survey was administered from August 27 to August 30, 2020, and, 1936 valid samples were received. Mental health was measured using the Brief Symptom Inventory (BSI-18). This study applied the ordinary least squares regression (OLS) model, and data analysis was performed using STATA. Results There were 1936 participants, with an equal distribution of genders. Multiple regression analysis showed that the mental health levels of rural youth were superior to those of urban youth (p = 0.049), especially when the epidemic was not severe (p = 0.013). Socioeconomic status had a significant positive promotion effect on mental health (p = 0.008), but the interaction effect between socioeconomic status and the urban–rural divide indicated that the promotion effect of socioeconomic status on the mental health of urban youth was greater than that of rural youth (p = 0.04). Social capital had a significant positive promotion effect on mental health (p = 0.000), and the interaction effect indicated that this promoting effect did not differ between urban and rural areas (p > 0.05).